Case studies of famous trials and the construction of guilt and innocence - Gorden, Caro (Bristol University Press, 2022)
"From the trials of Oscar Pistorius to O.J. Simpson and Michael Jackson, this innovative book provides a critical review of 11 high profile criminal cases. These case studies examine how 'guilt' and 'innocence' are constructed in the courts and in wider society, using the themes of evidence and narratives; credibility; rhetoric and oratory in the court room; social status; vulnerability and false confessions; diminished responsibility and the media and social judgments. Written for criminology, sociology, law and criminal justice students, the book includes: exercises to extend thinking on each case; recommended readings for studying the cases and concepts discussed in each chapter; an extensive specialist reference list including web links to videos and transcripts pertaining to many of the cases discussed in the book. The book delivers an accessible examination of the criminological, sociological, psychological and legal processes underpinning the outcome of criminal cases, and their representation in the media and wider society"--